Screening Consumers through Alternative Pricing Mechanisms - Eugenio J. Miravete (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
This paper addresses the optimal design of optional nonlinear tariffs. Two particular solutions commonly used in telecommunications and other industries are fully characterized. These optimal outlay schedules illustrate how the tariff design is altered when there exists a time lag between tariff choice and consumption. In this model consumers' uncertainty is resolved in the interim, between the tariff choice and the usage decision, through changes in their types. The paper studies whether the monopolist may profit from screening consumers according to different information sets, and it shows that expected profits are higher under an ex-post tariff if the variance of the ex-ante type distribution is large enough. The paper also shows that no results regarding social efficiency may be obtained in general. Welfare comparison of optional tariffs will be very sensitive to type distributions, how types enter demand specifications, and the relative variance of the type components.
Keywords: 330